Retraction: Singhal R, Rai B. sTNF-R Levels: Apical Periodontitis Linked to Coronary Heart Disease. Open Access Maced J Med Sci. 2017; 5(1):68-1 - Spiroski, Mirko (ID Design 2012/DOOEL Skopje, 2019)
[This retracts the article on p. 68 in vol. 5, PMID: 28293320.].